Dynamics of legal skills: Statutes, consititution and cases - Msabila, Dominik T. (Mzumbe University, 2025)
The book is divided into three parts as follows: Part A: Statutes and constitutional analysis; Part B: Legal cases; and Part C: Miscellaneous. The three parts generate twelve chapters as follows: Chapter One- Meaning and structure of statute; Chapter Two- Statute reading; Chapter Three- Statute writing and citation; Chapter Four- Statutory interpretation; Chapter Five- Presumptions and considerations in statutory interpretation; Chapter Six- Constitutional analysis; Chapter Seven- Meaning and structure of legal cases; Chapter Eight- Reading a case report; Chapter Nine- Writing a case note or case brief; Chapter Ten- Case citation; Chapter Eleven- Legal precis writing; and Chapter Twelve- Quotation, citation and referencing. Law students and other readers are encouraged to read this book as it will expose them to various legal skills that will be applied in analysing and understanding various legal documents.